A multifunctional targeting probe with dual-mode imaging and photothermal therapy used in vivo - Zhang, Xiao-Shuai (J Nanobiotechnology, 2018)
BACKGROUND: Ag(2)S has the characteristics of conventional quantum dot such as broad excitation spectrum, narrow emission spectrum, long fluorescence lifetime, strong anti-bleaching ability, and other optical properties. Moreover, since its fluorescence emission is located in the NIR-II region, has stronger penetrating ability for tissue. Ag(2)S quantum dot has strong absorption during the visible and NIR regions, it has good photothermal and photoacoustic response under certain wavelength excitation. RESULTS: 200 nm aqueous probe Ag(2)S@DSPE-PEG(2000)-FA (Ag(2)S@DP-FA) with good dispersibility and stability was prepared by coating hydrophobic Ag(2)S with the mixture of folic acid (FA) modified DSPE-PEG(2000) (DP) and other polymers, it was found the probe had good fluorescent, photoacoustic and photothermal responses, and a low cell cytotoxicity at 50 μg/mL Ag concentration. Blood biochemical analysis, liver enzyme and tissue histopathological test showed that no significant influence was observed on blood and organs within 15 days after injection of the probe. In vivo and in vitro fluorescence and photoacoustic imaging of the probe further demonstrated that the Ag(2)S@DP-FA probe had good active targeting ability for tumor. In vivo and in vitro photothermal therapy experiments confirmed that the probe also had good ability of killing tumor by photothermal. CONCLUSIONS: Ag(2)S@DP-FA was a safe, integrated diagnosis and treatment probe with multi-mode imaging, photothermal therapy and active targeting ability, which had a great application prospect in the early diagnosis and treatment of tumor. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12951-018-0367-9) contains supplementary material, which is available to authorized users.